2015
DOI: 10.1099/jmm.0.000128
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome in human immunodeficiency virus (HIV)-positive individuals

Abstract: Human immunodeficiency virus (HIV) infection is associated with a range of oral conditions, and increased numbers of disease-associated microbial species have previously been found in HIV-positive subjects. The aim of this study was to use next-generation sequencing to compare the composition of the oral microbiome in HIV-positive and -negative individuals. Plaque and saliva were collected from 37 HIV-positive individuals and 37 HIV-negative individuals, and their bacterial composition determined by pyrosequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 27 publications
3
64
2
1
Order By: Relevance
“…By contrast, while the bacterial community composition of oral wash specimens was unchanged in HIV-infected compared with healthy controls, using a deep sequencing approach, a difference in fungal communities was observed (167). A recent study on HIV-infected individuals undergoing ART has reported similar oral microbiomes but significant difference in the composition of the oral cavity microbiota (168). This study found that Haemophilus parainfluenza , which has been implicated in opportunistic infections, was associated with the HIV-infected individuals (168).…”
Section: Hiv and Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, while the bacterial community composition of oral wash specimens was unchanged in HIV-infected compared with healthy controls, using a deep sequencing approach, a difference in fungal communities was observed (167). A recent study on HIV-infected individuals undergoing ART has reported similar oral microbiomes but significant difference in the composition of the oral cavity microbiota (168). This study found that Haemophilus parainfluenza , which has been implicated in opportunistic infections, was associated with the HIV-infected individuals (168).…”
Section: Hiv and Oral Microbiomementioning
confidence: 99%
“…A recent study on HIV-infected individuals undergoing ART has reported similar oral microbiomes but significant difference in the composition of the oral cavity microbiota (168). This study found that Haemophilus parainfluenza , which has been implicated in opportunistic infections, was associated with the HIV-infected individuals (168). A most recent study utilizing Microarray and pyrosequencing techniques reported a significant difference in the prevalence and distribution of the saliva bacterial communities among HIV-infected individuals before and after initiation of ART (169).…”
Section: Hiv and Oral Microbiomementioning
confidence: 99%
“…Although many studies have been devoted to HIV in the genital tract, the connection between HIV, oral microbiome, and periodontal disease has also drawn the attention of the scientific community [113116] [105,106]. Recent works have found associations between periodontitis, a chronic inflammatory disease of the periodontium occurring in response to bacterial infection, and several types of oral cancers [117120].…”
Section: Oral Microbiomementioning
confidence: 99%
“…A number of authors have studied the oral microbiota of HIV‐1‐infected individuals using gene amplicon sequencing (Beck et al, ; Dang et al, ; Goldberg et al, ; Kistler, Arirachakaran, Poovorawan, Dahlen, & Wade, ; Li et al, ; Noguera‐Julian et al, ; Presti et al, ; Starr et al, ); however, only two papers have been published regarding the oral microbiome of HIV‐1‐infected children (Goldberg et al, ; Starr et al, ). These studies were carried out with HIV‐1‐infected children from the United States, by the use of 454 pyrosequencing (Goldberg et al, ) or Illumina platform on a MiSeq (Starr et al, ).…”
Section: Introductionmentioning
confidence: 99%